A Study of Customer Resonance and Loyalty: The Moderating Role of Brand Value Among Used BMW Car Owners - Ammalia, Nuuru Rizky; Sabar, Sabar; Wardhana, Mahendra; Wahyudie, Prasetyo (Publikasi Indonesia, 2025)
The luxury automotive industry in Indonesia continues to demonstrate stable growth despite economic pressures and technical challenges, particularly in classic models. BMW, as a dominant luxury car brand, has successfully maintained user loyalty, including for older models such as the E46 and F30. This study aims to analyze the influence of brand experience, brand trust, and brand image on customer loyalty, with brand resonance as a mediating variable and brand value as a moderating variable. A quantitative approach was employed by distributing online questionnaires to users of BMW 3 Series (E46 and F30) in Surabaya, Jakarta, Bekasi, and Solo. Data were analyzed using structural equation modeling (SEM) with AMOS 26. The results indicate that brand experience and brand trust have a positive and significant effect on brand resonance, while brand image does not have a significant effect. Brand resonance was found to significantly mediate the relationship with customer loyalty. Brand value also positively moderates the relationship between brand resonance and customer loyalty. These findings highlight the importance of emotional experience, community involvement, and perceived brand value in fostering loyalty, even for vehicles that are not the owners’ primary cars. This study emphasizes that loyalty is shaped not only by functional satisfaction but also by long-term emotional attachment, particularly in the context of classic luxury cars.